Husserl and Merleau-Ponty: A Feminist Critique of the Phenomenological Body - Makhlouf, Jasmin M. (AUC Knowledge Fountain, 2021)
The purpose of this thesis is to explore the phenomenological notion of embodiment, to explain the objectification and coercion that women and their bodies experience on a daily basis. I build the philosophical foundation of this thesis on Husserlian and Merleau-Pontian phenomenology, as well as, their work’s receptions in feminist philosophy of the early 20th century, mainly Simone de Beauvoir, as well as, more contemporary thinkers like Luce Irigaray and Judith Butler. Moreover, the thesis argues for a return to the traditional phenomenological notion of embodiment while incorporating elements of sexuality and sexual difference.